Solid State Devices : the six invited papers presented at the Third European Solid State Device Research Conference (ESSDERC) - European Solid State Device Research Conference (Bristol : The Institute of Physics, 1971)
Contains invited papers presented at the European Solid State Device Research Conference.
Began with vol. for 1971. Cf. New serial titles.
Annual
Keywords: Semiconductors -- Congresses